Peningkatan Pemahaman Masyarakat Sodong, Kabupaten Bandung Barat dalam Pencegahan dan Penanganan ISPA melalui Program Pengabdian Masyarakat - Yura Witsqa Firmansyah; Hastin Atas Asih; Violletha Shefierra; Ewutia Sanara; Windy Supri Alfian; Hani Handayani (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
According to the 2023 Indonesian Health Survey, the incidence of Upper Respiratory Tract Infection (URTI) in West Java reached 156,977 cases. This high prevalence reflects a significant public health challenge, influenced by population density and environmental factors that facilitate the spread of the disease. As a strategic intervention, this community empowerment program aims to assess and enhance public knowledge regarding URTI prevention and management. The initiative was designed as an educational solution utilizing the field school method and educational brochures. The program was implemented on Friday, December 20, 2024, in the Jalan Sodong area, West Bandung Regency, involving 10 respondents. The program’s outcomes indicated a substantial improvement in community knowledge. Prior to the intervention, the average knowledge score was 46.5, which significantly increased to 95.5 after participation, reflecting a 91.45% increase. This notable improvement serves as a key factor in strengthening public awareness and preparedness in preventing URTI. Thus, the application of the field school method combined with educational brochures has proven to be an effective approach in increasing public awareness of URTI. This initiative contributes to disease prevention efforts, with the potential for broader implementation to reduce the incidence of URTI in other communities.